2018
DOI: 10.1155/2018/4579734
|View full text |Cite
|
Sign up to set email alerts
|

Chicken Is a Useful Model to Investigate the Role of Adipokines in Metabolic and Reproductive Diseases

Abstract: Reproduction is a complex and essential physiological process required by all species to produce a new generation. This process involves strict hormonal regulation, depending on a connection between the hypothalamus-pituitary-gonadal axis and peripheral organs. Metabolic homeostasis influences the reproductive functions, and its alteration leads to disturbances in the reproductive functions of humans as well as animals. For a long time, adipose tissue has been recognised as an endocrine organ but its ability t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 212 publications
(228 reference statements)
3
45
1
2
Order By: Relevance
“…In a previous study we showed that plasma RARRES2 was significantly associated to fattening in reproductive hens [55]. Furthermore, NAMPT has been described as more a myokine than an adipokine [55,56]. Here, we showed that dietary GSE supplementation decreases plasma RARRES2 whereas it increases plasma ADIPOQ and NAMPT in each period (from starting to laying period).…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…In a previous study we showed that plasma RARRES2 was significantly associated to fattening in reproductive hens [55]. Furthermore, NAMPT has been described as more a myokine than an adipokine [55,56]. Here, we showed that dietary GSE supplementation decreases plasma RARRES2 whereas it increases plasma ADIPOQ and NAMPT in each period (from starting to laying period).…”
Section: Discussionsupporting
confidence: 55%
“…We observed that plasma RARRES2 and ADIPOQ were negatively correlated with live body weight whereas the opposite was observed for the plasma NAMPT. In a previous study we showed that plasma RARRES2 was significantly associated to fattening in reproductive hens [55]. Furthermore, NAMPT has been described as more a myokine than an adipokine [55,56].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a previous study, we showed that the measure of back fat thickness by ultrasound is a good predictive marker of the adipose tissue content in the whole body of broilers [6]. Furthermore, in another study, we showed a negative correlation between adiponectin concentrations and fattening, but also a positive correlation with chemerin concentrations in plasma and fatness [43]. So, the use of GSE in the diet could decrease adiposity in female broilers during the reproductive period.…”
Section: Time/concentration Exposurementioning
confidence: 76%
“…Значительные успехи в оценке роли висфатина в контроле функций яичников были достигнуты при изучении его влияния на стероидогенез и фолликулогенез у птиц. Это обусловлено тем, что яичники птиц являются наиболее подходящей моделью для изучения регуляторных эффектов адипокинов как на метаболические процессы, так и на функции репродуктивной системы [53]. Следует, однако, отметить, что эффекты висфатина на ГГГ-ось характеризуются видовой специфичностью, вследствие чего экстраполировать данные, полученные при изучении птиц, на человека нужно с большой осторожностью.…”
Section: влияние висфатина на женскую репродуктивную системуunclassified